Explorations in urban design : an urban design research primer - Carmona, Matthew (Ashgate, 2014)
This book advances an interdisciplinary and innovative approach to urban design, whilst recognising that distinctly different traditions exist within its study and practice. It informs users who are grappling with urban design research problems, but who need the inspiration to move from idea to methodological approach. Through the work of 32 urban researchers from the arts, sciences and social sciences, it demonstrates a wide range of problems and approaches and shows how the diverse range of complementary approaches can come together to provide a holistic understanding to the design of cities.